Differential integrin activity mediated by platelet collagen receptor engagement under flow conditions - Pugh, Nicholas; Maddox, Ben D.; Bihan, Dominique; Taylor, Kirk A.; Mahaut-Smith, Martyn P.; Farndale, Richard W. (Thrombosis and Haemostasis, 2017)
The platelet receptors glycoprotein (Gp)VI, integrin α2β1 and GpIb/V/IX mediate platelet adhesion and activation during thrombogenesis. Increases of intracellular Ca2+ ([Ca2+]i) are key signals during platelet activation; however, their relative importance in coupling different collagen receptors to functional responses under shear conditions remains unclear. To study shear-dependent, receptor-specific platelet responses, we used collagen or combinations of receptor-specific collagen-mimetic peptides as substrates for platelet adhesion and activation in whole human blood under arterial flow conditions and compared real-time and endpoint parameters of thrombus formation alongside [Ca2+]i measurements using confocal imaging. All three collagen receptors coupled to [Ca2+]i signals, but these varied in amplitude and temporal pattern alongside variable integrin activation. GpVI engagement produced large, sustained [Ca2+]i signals leading to realtime increases in integrins α2β1− and αIIbβ3-mediated platelet adhesion. αIIbβ3-dependent platelet aggregation was dependent on P2Y12 signalling. Co-engagement of α2β1 and GpIb/V/IX generated transient [Ca2+]i spikes and low amplitude [Ca2+]i responses that potentiated GpVI-dependent [Ca2+]i signalling. Therefore α2β1 GpIb/V/IX and GpVI synergise to generate [Ca2+]i signals that regulate platelet behaviour and thrombus formation. Antagonism of secondary signalling pathways reveals distinct, separate roles for αIIbβ3 in stable platelet adhesion and aggregation.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Platelet glycoproteins; collagen receptors; signal transduction; thrombosis; fluid shear